Characterization of a single mutation in TraQ in a strain of Escherichia coli partially resistant to Qβ infection - Kashiwagi, Akiko; Kitamura, Hikari; Sano Tsushima, Fumie (Frontiers in Microbiology, 2015)
Bacteria and virulent bacteriophages are in a prey–predator relationship. Experimental models under simplified conditions with the presence of bacteria and bacteriophages have been used to elucidate the mechanisms that have enabled both prey and predator to coexist over long periods. In experimental coevolution conducted with Escherichia coli and the virulent RNA bacteriophage Qβ in serial transfer, both coexisted for at least for 54 days, during which time they continued to change genetically and phenotypically. By day 16, an E. coli strain partially resistant to Qβ appeared and caused an approximately 10^4-fold decrease in Qβ amplification. Whole-genome analysis of this strain suggested that a single mutation in TraQ was responsible for the partially resistant phenotype. TraQ interacts with propilin, encoded by the traA gene and a precursor of pilin, which is a component of the F pilus. The present study was performed to elucidate the mechanism underlying the coexistence of E. coli and Qβ by investigating how a mutation in TraQ altered the physiological state of E. coli, and thus the amplification of Qβ. Overexpression of wild-type TraQ in the partially resistant E. coli strain resulted in recovery of both TraA protein content, including propilin and pilin, and Qβ amplification to levels comparable to those observed in the susceptible strain. Intriguingly, overexpression of the mutant TraQ in the partially resistant strains also increased the levels of TraA protein and Qβ amplification, but these increases were smaller than those observed in the wild-type strain or the partially resistant strain expressing wild-type TraQ. The results of this study represent an example of how E. coli can become partially resistant to RNA bacteriophage infection via changes in a protein involved in maturation of a receptor rather than in the receptor itself and of how E. coli can stably coexist with virulent RNA bacteriophages.